1994
DOI: 10.1017/s0960258500002245
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation tolerance in two species with recalcitrant seeds: Clausena lansium (Lour.) and Litchi chinensis (Sonn.)

Abstract: 1994). Desiccation tolerance in two species with recalcitrant seeds: Clausena lansium (Lour.) and Litchi chinensis (Sonn.). AbstractSeeds were collected at weekly intervals from mid-maturation to the fully ripened stage As seed development progressed, desiccation tolerance increased Desiccation tolerance of C lansium seeds was greatest at 67 days after anthesis (DAA), when they tolerated air drying for 9 days; 74 DAA was considered as physiological maturity, and their full viability was only maintained for up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
1
11
0
1
Order By: Relevance
“…It is equal to 50% in cork oak (Finch-Savage and Blake, 1994) and 45% in litchee, another plant with recalcitrant seeds (Fu et al, 1994). Water status enables a distinction to be made between recalcitrant and orthodox seeds whose water content can be as low as a few percent: 6.9%, for example, in Ricinus (Kermode and Bewley, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…It is equal to 50% in cork oak (Finch-Savage and Blake, 1994) and 45% in litchee, another plant with recalcitrant seeds (Fu et al, 1994). Water status enables a distinction to be made between recalcitrant and orthodox seeds whose water content can be as low as a few percent: 6.9%, for example, in Ricinus (Kermode and Bewley, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Germination percentage is usually used as an index of desiccation tolerance (Koster and Leopold, 1988;Blackman et al, 1991;Fu et al, 1994). However, sometimes the germination percentage is inappropriate as when immature seeds are unable to germinate.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the membrane of embryonic axes at physiological maturity was unimpaired and more tolerant to desiccation, but those of immature and overripe ones was less tolerant. The dry weight ofwampee seeds increased rapidly from 50 to 70 DAA (Fu et al, 1994), but protein synthesis rate decreased in later stages of development (data not shown).…”
Section: Heat Stable Proteins and Desiccation Tolerance In Wampee Seedmentioning
confidence: 91%
See 2 more Smart Citations